Elizabethkingia Infections in Humans: From Genomics to Clinics - Jiun-Nong Lin; Chung-Hsu Lai; Chih-Hui Yang; Yi-Han Huang (Microorganisms, 2019)
The genus Elizabethkingia has recently emerged as a cause of life-threatening infections in humans, particularly in immunocompromised patients. Several new species in the genus Elizabethkingia have been proposed in the last decade. Numerous studies have indicated that Elizabethkingia anophelis, rather than Elizabethkingia meningoseptica, is the most prevalent pathogen in this genus. Matrix-assisted laser desorption/ionization−time of flight mass spectrometry systems with an extended spectrum database could reliably identify E. anophelis and E. meningoseptica, but they are unable to distinguish the remaining species. Precise species identification relies on molecular techniques, such as housekeeping gene sequencing and whole-genome sequencing. These microorganisms are usually susceptible to minocycline but resistant to most β-lactams, β-lactam/β-lactam inhibitors, carbapenems, and aminoglycosides. They often exhibit variable susceptibility to piperacillin, piperacillin-tazobactam, fluoroquinolones, and trimethoprim-sulfamethoxazole. Accordingly, treatment should be guided by antimicrobial susceptibility testing. Target gene mutations are markedly associated with fluoroquinolone resistance. Knowledge on the genomic characteristics provides valuable insights into in these emerging pathogens.